Walking Behavior and Perceived Physiological Wellness Through the Lens of the Theory of Planned Behavior - Mondoy, Hazel Kate Shulamitte (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between walking behavior and perceived physiological wellness among adults walking at Dipolog Boulevard. The research was anchored on the Theory of Planned Behavior and the Health Belief Model, which explain how attitudes, social influences, and perceived control shape walking behavior. A quantitative, cross-sectional, descriptive-correlational design was used with 100 purposively sampled adults aged 18 and above. Data were collected using a structured self-administered questionnaire assessing walking frequency, duration, distance, planned walking behavior, and dimensions of physiological wellness including cardiovascular endurance, muscular strength, metabolic regulation, and weight management. Findings revealed that respondents engaged in moderate walking frequency and duration, demonstrated positive attitudes, low subjective norms, and low perceived behavioral control. Physiological wellness was high in cardiovascular endurance and muscular strength, but lower in metabolic regulation and weight management. Correlation and regression analyses indicated no significant relationship between planned walking behavior and perceived physiological wellness, and no TPB component significantly predicted wellness outcomes. The study concluded that behavioral intentions alone may not translate directly into physiological wellness. It recommended interventions that enhance social support and perceived behavioral control to sustain walking engagement. The research supports Sustainable Development Goal 3 by promoting community health and SDG 11 by encouraging active and accessible public spaces. Its sustainability impact lies in fostering community well-being, informing urban planning for health-promoting environments, and enhancing social and public health initiatives.